Soil organic carbon variability in tropical cropping systems: interactions with texture, pH, macronutrients, and organic matter - Solórzano Acosta, Richard Andi (2026)
Soil organic carbon (SOC) plays a crucial role in mitigating climate change and enhancing soil fertility. Its storage and dynamics are particularly significant in agricultural ecosystems of the Peruvian Amazon, where the expansion of agriculture and livestock farming may disrupt the regional carbon balance. This study aimed to analyze SOC variability and its relationship with edaphic and nutritional properties in agricultural systems in Eastern Peru (San Martín and Loreto regions). Four representative cropping systems were evaluated: coffee grown in agroforestry and polyculture systems; maize as a monoculture; and camu-camu and cocoa cultivated in monoculture and agroforestry systems, respectively. The highest SOC content (80.70 t·ha−1), phosphorus (12.03 mg·kg−1), and moisture (52.36%) were observed in coffee-growing soils, likely due to the presence of shade trees that enhance organic matter inputs in soils at 0–20 cm depth. In contrast, soils under maize cultivation exhibited the highest levels of nitrogen (0.19%), potassium (364.02 mg·kg−1), and pH (7.61), likely due to the frequent fertilization applied to this crop. The lowest carbon saturation deficits were found in soils under camu-camu (31.67%), cocoa (26.88%), maize (24.80%), and coffee (20.59%), with the most pronounced deficits occurring in camu-camu and cocoa soils in Yurimaguas (Loreto), indicating a heightened vulnerability to carbon loss. These findings underscore the significant influence of crop type and management practices on carbon and nutrient dynamics in tropical soils. Long-term studies are recommended to assess carbon sequestration over extended periods, informing sustainable soil management policies in the Peruvian Amazon.